PELATIHAN IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH INKLUSI - Ana Rafikayati; Lutfi Isni Badiah; Farisah Dianah Alifah; Irine Balgis Salsabila (Kanigara, 2022)
This community service is targeted to Musyawarah Guru Pendidikan Khusus (MGPK) Kota Surabaya, totaling 35 Guru Pendamping Khusus (GPK). The problem faced by partners is the lack of information related to the Kurikulum Merdeka which is now the focus of the school. Especially for special education where there is not much info related to it. Seeing these problems, the service team provided a solution in the form of training on the implementation of the Kurikulum Merdeka to target partners. The training is carried out online and offline. The implementation of community service consists of activities, namely: 1) online training , 2) offline training, and 3) assistance. This community service was held from April 1 to April 31, 2022. The result of this community service program is an increase in knowledge about the implementation of Kurikulum Merdeka and an increase in the skills of participants in compiling an teaching module.